Effects of Vinpocetine on Random Skin Flap Survival in Rats - Xiao-Xiao, Tao; Sen-Min, Wu; Ding-Sheng, Lin (Journal of Reconstructive Microsurgery, 2013)
The effect of vinpocetine on flap survival, vascular endothelial growth factor (VEGF) expression, and superoxide dismutase (SOD) and malondialdehyde (MDA) contents were evaluated in this study. The McFarlane flap model was established in 20 rats and evaluated within two groups. Postoperative celiac injection was given for 7 days in the two groups: vinpocetine was applied in Group 1, and the same volume of saline was applied in Group 2. Flap necrosis was measured on day 7 by cellophane in all groups. VEGF expression was determined using immunohistochemical methods on tissue samples taken after 7 days of injections. SOD and MDA contents were examined according to the Kit (reagent instructions). Vinpocetine significantly reduced necrosis area in Group 1 (p < 0.05). VEGF expression and SOD contents were significantly increased in Group 1 compared with Group 2 (p < 0.01), whereas MDA level was reduced (p < 0.05). This experimental study demonstrates that vinpocetine improves survival of random skin flaps, promotes neovascularization, and increases VEGF expression. Meanwhile, vinpocetine has a protective effect against ischemia-reperfusion injury by improving SOD vitality and decreasing MDA value.
Keywords: vinpocetine; random skin flap; survival; vascular endothelial growth factor; free radical